Finding freedom [compact disc, unabridged] : a cook's story; remaking a life from scratch - French, Erin (Chef) (Macmillan Audio, 2021)
From Erin French, owner and chef of the critically acclaimed The Lost Kitchen, a TIME world dining destination, a life-affirming memoir about survival, renewal, and finding a community to lift her up.